The International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT): Model description for version 3 - Robinson, Sherman; Mason-D’Croz, Daniel; Islam, Shahnila; Sulser, Timothy B.; Robertson, Richard D.; Zhu, Tingju; Gueneau, Arthur; Pitois, Gauthier; Rosegrant, Mark W. (International Food Policy Research Institute, 2015)
The International Food Policy Research Institute’s International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) supports analysis of long-term challenges and opportunities for food, agriculture, and natural resources at global and regional scales. IMPACT is continually being updated and improved to better inform the choices that decisionmakers face today. This document describes the latest version of the model. IMPACT version 3 expands the geographic and commodity scope of the model in response to desires expressed by researchers and policymakers to address more complex questions involving climate change, food security, and economic development into the future. IMPACT 3 is an integrated modeling system that links information from climate models (Earth System Models), crop simulation models (for example, Decision Support System for Agrotechnology Transfer), and water models linked to a core global, partial equilibrium, multimarket model focused on the agriculture sector. This model system supports longer-term scenario analysis through the integration of these multidisciplinary modules to provide researchers and policymakers with a flexible tool to assess and compare the potential effects of changes in biophysical systems, socioeconomic trends, technologies, and policies.